Diversity of palms (Palmae) in Gunung Lumut, Central Kalimantan - JOKO RIDHO WITONO (Biodiversitas Journal of Biological Diversity, 2005)
Kalimantan is one of biodiversity centers in Indonesia, especially for commercial timbers such as dipterocars and commercial non timbers, such as orchids, ferns, and palms. One of the biodiversity centers in Kalimantan is Gunung Lumut. Gunung Lumut is located in Barito Utara Regency, Central Kalimantan. The area is proposed as conservation area (world natural heritage) by local government, because its biodiversity richness and also water reserve. Biodiversity surveys on plants and animals have been done by Indonesian Institute of Sciences staff cooperation with the Local government since 2002 to get some data for that purposed. Based on the survey on palms taxa, Gunung Lumut has 33 species of palms in 11 genera. There are Calamus 8 species, Daemonorops 7 species, Plectocomia 1 species, Korthalsia 6 species, Ceratolobus 2 species, Eugeissona 1 species, Oncosperma 1 species, Pinanga 4 species, Iguanura 1 species, Arenga 1 species, and Licuala 1 species.@ 2005 Jurusan Biologi FMIPA UNS SurakartaKey words: palms, Gunung Lumut, Kalimantan, world natural heritage.